PENGARUH INTENSITAS BERMAIN GAME ONLINE TERHADAP MENTAL EMOSIONAL PADA ANAK SEKOLAH DI MADRASAH IBTIDAIYAH REJODADI CILACAP - Adroni Adroni; Wasis Eko Kurniawan; Ema Wahyu Ningrum (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The use of online games is increasingly widespread among school-age children, including those at the Madrasah Ibtidaiyah level. There are concerns that high levels of play could impact children's mental and emotional well-being, which is a crucial aspect of their psychosocial development. This study aims to determine the effect of the intensity of playing online games on the emotional mental health of school children at Madrasah Ibtidaiyah Rejodadi Cilacap. This study used a quantitative design with a cross-sectional approach. The sample consisted of 173 students and was selected using a total sampling technique. The instruments used were an online gaming intensity questionnaire and the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed univariately and bivariately using the Spearman Rank test. Most children have high online gaming intensity (52.6%) and normal emotional mental condition (56.6%), although 43.4% are in the borderline category. Statistical test results show a very strong and significant relationship between online gaming intensity and children's emotional mental condition (r = 0.750; p = 0.000). Conclusion: The higher the intensity of playing online games, the greater the risk of mental and emotional disorders in school children. Therefore, support and supervision from parent and theachers are essential to limit playing time and provide education about the impact of online games on mental health.